Endosomal escape and cytosolic penetration of macromolecules mediated by synthetic delivery agents - Brock, Dakota J. (Bioconjug Chem, 2018)
Cell delivery reagents often exploit the endocytic pathway as a route of cell entry. Once endocytosed, these reagents must overcome endosomal entrapment to insure the release of their macromolecular cargos into the cytosol of cells. In this review, we describe several examples of prototypical synthetic reagents that are capable of endosomal escape and examine their mechanisms of action, their efficiencies, and effects on cells. Although these delivery systems are chemically distinct, some commonalities in how they interact with cellular membranes can be inferred. This, in turn, sheds some light on the process of endosomal escape, and may help guide the development and optimization of next-generation delivery tools.